2023
DOI: 10.1002/job.2729
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of turnover amongst volunteers: A systematic review and meta‐analysis

Vivien W. Forner,
Djurre Holtrop,
Edwin J. Boezeman
et al.

Abstract: SummaryVolunteers represent a global workforce equivalent to 61 million full‐time workers. A significant decline in volunteering has highlighted the urgency to better understand and address turnover amongst volunteers. To address this, we conducted a systematic review and meta‐analysis of turnover amongst volunteers. We also examined whether staying or leaving has different predictors. The meta‐analysis integrated and synthesized 117 studies, encompassing 1104 effect sizes across 55 335 volunteer workers, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…A study by Boezeman and Ellemers (2007) showed a stronger positive relation of normative commitment with volunteers' intention to remain with the organization than affective commitment. In contrast, a recent meta-analysis by Forner et al (2024) found no relation between normative commitment and a turnover estimate that combined stay/leave indicators.…”
Section: Organizational Commitment In Community-based Volunteering (S...mentioning
confidence: 79%
See 1 more Smart Citation
“…A study by Boezeman and Ellemers (2007) showed a stronger positive relation of normative commitment with volunteers' intention to remain with the organization than affective commitment. In contrast, a recent meta-analysis by Forner et al (2024) found no relation between normative commitment and a turnover estimate that combined stay/leave indicators.…”
Section: Organizational Commitment In Community-based Volunteering (S...mentioning
confidence: 79%
“…Research in the volunteering (sports) sector was largely in line with the theory, revealing a positive connection between volunteers' affective commitment and job satisfaction (Bang et al, 2012), work performance (Hoye, 2007;Stephens et al, 2004), and intention to remain affiliated with the organization (see meta-analysis of Forner et al, 2024;Holtrop et al, 2024). Also normative commitment connected positively to work performance (Stephens et al, 2004), yet this relation was, as expected, less pronounced when compared to affective commitment.…”
Section: Organizational Commitment In Community-based Volunteering (S...mentioning
confidence: 87%
“…These findings are unique in their demonstration of how on-and off-the-JE exhibit dissimilar moderating effects and how on-the-JE might not always be beneficial, to the extent that it "can leave employees in a precarious position by feeling "stuck" under a looming threat of involuntary job loss (Peltokorpi & Allen, 2024, p. 423). Forner et al (2024) extend the special issue's focus to another critical sector grappling with retention issues-volunteering. Through a systematic review and meta-analysis (which includes 117 studies), they provide the most comprehensive examination of volunteer turnover to date, distinguishing between drivers of leaving and staying.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…The observed differences between reasons for staying versus leaving-though limited-are nevertheless a distinguishing highlight of the paper. Forner et al (2024) advance novel understanding of employee retention and turnover, which often are considered opposite ends of a single continuum.…”
Section: Papers In This Special Issuementioning
confidence: 99%